24.1: Invited Paper: Flexible Oxide TFTs for Bendable and flexible displays. (28th November 2018) - Jang, Jin; Lee, Suhui
Abstract : We review in this talk the highly stable, high performance E/S a‐IGZO TFT on plastic substrate by using split active and S/D electrodes. The TFTs exhibit high mobility of 74 cm 2 /Vs and extremely stable behavior under bias‐stress and mechanical stress. The TFT process is same as conventional one with only design change. Therefore, this technology can be used for the manufacturing of flexible and bendable AMOLED on plastic substrate